Effect of football activity and physical fitness on information processing, inhibitory control and working memory in adolescents - Ryan A. Williams; Simon B. Cooper; Karah J. Dring; Lorna Hatch; John G. Morris; Caroline Sunderland; Mary E. Nevill (BMC Public Health, 2020)
Abstract Background Whilst an acute bout of exercise has been shown to enhance subsequent cognition, including in adolescents, the effects of team games (of which Football is the most popular) has received little attention. Therefore, this study examined: the effect of an acute bout of outdoor Football activity on information processing, inhibitory control, working memory and circulating brain-derived neurotrophic factor (BDNF) in adolescents; the effect of physical fitness on cognition and; the moderating effect of physical fitness on the acute exercise responses. Methods Following familiarisation, 36 adolescents (16 girls) took part in two trials (60-min Football and 60-min seated rest) separated by 7-d in a counterbalanced, crossover design. Information processing and inhibitory control (Stroop Test), and working memory (Sternberg Paradigm) were assessed 30-min before exercise/rest and immediately, 45- and 90-min post-exercise/rest. Capillary blood samples were obtained before exercise/rest and up to 120-min post-exercise/rest. The median split of distance covered on the MSFT was used to divide the group into high- and low-fit groups. Results Performance on the cognitive function tasks was similar between Football and seated rest (trial*time interactions; all p > .05). However, the high-fit group had overall quicker response times on both levels of the Stroop Task and all three levels of the Sternberg Paradigm (main effect of fitness; all p < .001). Furthermore, the exercise-cognition relationship was moderated by physical fitness, with improvements in working memory response times seen post-exercise, only in the high-fit group (trial*time*fitness interaction, p < .05). Circulating BDNF was unaffected by the Football activity and physical fitness (p > .05). Conclusion The present study shows that higher levels of physical fitness are beneficial for cognitive function and provides novel evidence that an ecologically valid, and popular, form of exercise is beneficial for working memory following exercise, in high-fit participants only.